Green Marketing, Kualitas Pelayanan, Word of Mouth, Keputusan Pembelian Minuman Kopi - Murtiningsih, Dewi; Putra, Yananto Mohadi (Neolectura, 2023)
This study aims to determine the: does green marketing influence purchase decission?, does servive quality influence purchase decission?, does word of mouth influence purchase decission?, does green marketing, service quality, word of mouth influence purchase decission?. The type of research is descriptive association, the sample of this study includes 100 respondents determined by the MLE formula, and researcher use a sample of 110 with the consideration that if there was a defect in the questionnaire then the sample size would still ben fullfilled; the sampling technique is simple random sampling; the data is obtained by distributing a questionnaire and then analyzing it using SPSS Version 26. Green marketing influence purchase decission, service quality influence purchase decission, word of mouth influence purchase decission; green marketing, service quality, word of mouth influence purchase decission. Future research is expected to add the number of samples, expand the research object, and add relevant topics; future research is expected to process data with different analysis tools.